Pengaruh Employer Branding dan Kompensasi terhadap Minat Melamar Kerja pada Generasi Z di Daerah Istimewa Yogyakarta - Aisyah Nur Jannavi; Kristiana Sri Utami (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of employer branding and compensation on job application interest among Generation Z in the Special Region of Yogyakarta. The background of this research is the phenomenon known as the "War for Talent," which refers to the competition among companies to attract the best talent. Currently, the workforce is dominated by Generation Z, which brings unique characteristics and job expectations, requiring companies to adopt strategies and understand the factors that can attract top talent. This research employs a quantitative approach. The type and source of data used are primary data. The population in this study consists of Generation Z individuals in the Special Region of Yogyakarta. The sample size includes 100 respondents. The data were analyzed using multiple linear regression analysis. The results of this study indicate that: (1) Employer branding has a positive and significant partial effect on job application interest (Y) among Generation Z in the Special Region of Yogyakarta; (2) Compensation has a positive and significant partial effect on job application interest (Y) among Generation Z in the Special Region of Yogyakarta; and (3) Employer branding and compensation (X2), collectively, have a positive and significant effect on job application interest (Y) among Generation Z in the Special Region of Yogyakarta.